Nutritional, microbiological and pharmacological properties of Moringa oleifera - Romero, Aurora Martínez; Sánchez, José Luis Ortega; Cervantes-Flores , Maribel; Alba-Romero, José de Jesús (Seven Editora, 2023)
Moringa oleifera is a multipurpose herbal tropical plant, an alternative with therapeutic purposes and with great impact as a sustainable strategy within the UN Agenda 2030, within its second sustainable development goal (SDG) Zero Hunger. The objective of the present literature review was to know the nutritional, microbiological and pharmacological properties of M. oleifera. M. oleifera is a promising tree in solving food safety problems used in the preparation of food for human consumption. M. oleifera contains phytochemicals in leaves, seeds and pods, glycosides, polyphenols, tannins, flavonoids and derivatives, components such as essential amino acids, carotenoids and anthocyanidins that provide the plant with nutritional, functional, and pharmacological properties with antimicrobial, hypotensive, and antioxidant activities. hypoglycemic, immunomodulatory, and anti-inflammatory. Moringa leaves contain fiber, ash, carbohydrates, total proteins, lipids, minerals such as sodium, potassium, magnesium, phosphorus, iron, zinc, copper, calcium, and manganese. M. oleifera brings with it the solution to problems of the general population such as malnutrition, environmental pollution, and diseases that affect humanity. DOI:https://doi.org/10.56238/interdiinovationscrese-076